Cortisol stimulates arginine vasotocin and isotocin release from the hypothalamo‐pituitary complex of round goby (Neogobius melanostomus): Probable mechanisms of action. Issue 9 (14th July 2015) - Kalamarz‐Kubiak, Hanna; Kleszczyńska, Agnieszka; Kulczykowska, Ewa
Abstract There were two aims of this in vitro perfusion study. Firstly, to determine which class of receptors, glucocorticoid (GRs) or mineralocorticoid (MRs), are involved in cortisol regulation of arginine vasotocin (AVT) and isotocin (IT) release from the hypothalamo‐pituitary (H–P) complex of round goby (Neogobius melanostomus). Secondly, to determine which pathways, genomic or non‐genomic, are involved in the aformentioned process.The H–P explants were perfused with cortisol (1.4 × 10−7 M, 2.8 × 10−7 M, 0.4 × 10−6 M); only the highest dose significantly increased a release of both nonapeptides. In the perfusion of H–P explants, we used cortisol (0.4 × 10−6 M) in combination with GRs antagonist RU486 (0.3 × 10−6 M) or MRs antagonist C03DA01 (0.36 × 10−6 M) or transcription inhibitor Actinomycin D (1 × 10−7 M). All inhibitors were also tested seperately. The contents of AVT and IT in the perfusion media was determined by high‐performance liquid chromatography (HPLC) with UV detection. This study suggested that different mechanisms were involved in the regulation of AVT and IT release from H–P complex in round goby. Apparently it was GRs but not MRs that were involved in cortisol regulation of AVT and IT release. In the case of AVT, our data points to both genomic and non‐genomic pathways mediating the effect of cortisol; in the case of IT, it is only the non‐genomic pathway. This study presents the first feasible mechanisms of cortisol action on AVT and IT release from the H–P complex in round goby. J. Exp. Zool. 323A: 616–626, 2015. © 2015 Wiley Periodicals, Inc.